Radiosynthesis of O‐(1‐[18F]fluoropropan‐2‐yl)‐O‐(4‐nitrophenyl)methylphosphonate: A novel PET tracer surrogate of sarin. (4th November 2018) - Hayes, Thomas R.; Thompson, Charles M.; Blecha, Joseph E.; Gerdes, John M.; VanBrocklin, Henry F.
Abstract : O‐(1‐Fluoropropan‐2‐yl)‐O‐(4‐nitrophenyl) methylphosphonate is a reactive organophosphate ester (OP) developed as a surrogate of the chemical warfare agent sarin that forms a similar covalent adduct at the active site serine of acetylcholinesterase. The radiolabeled O‐(1‐[ 18 F]fluoropropan‐2‐yl)‐O‐(4‐nitrophenyl) methylphosphonate ([ 18 F] fluorosarin surrogate) has not been previously prepared. In this paper, we report the first radiosynthesis of this tracer from the reaction of bis ‐(4‐nitrophenyl) methylphosphonate with 1‐[ 18 F]fluoro‐2‐propanol in the presence of DBU. The 1‐[ 18 F]fluoro‐2‐propanol was prepared by reaction of propylene sulfite with Kryptofix 2.2.2 and [ 18 F] fluoride ion. The desired tracer O‐(1‐[ 18 F]fluoropropan‐2‐yl)‐O‐(4‐nitrophenyl) methylphosphonate was obtained in a >98% radiochemical purity with a 2.4% ± 0.6% yield (n = 5, 65 minutes from start of synthesis) based on starting [ 18 F] fluoride ion and a molar activity of 49.9 GBq/μmol (1.349 ± 0.329 Ci/μmol, n = 3). This new facile radiosynthesis routinely affords sufficient quantities of [ 18 F] fluorosarin surrogate in high radiochemical purity, which will further enable the tracer development as a novel radiolabeled OP acetylcholinesterase inhibitor for assessment of OP modes of action with PET imaging in vivo. Abstract : Synthesis of a fluorine‐18‐labeled PET tracer surrogate of sarin to evaluate the exposure mechanism and reactivation of acetylcholinesterase.